KREATIVITAS TARI BERBASIS LINGKUNGAN PADA KEGIATAN PENGEMBANGAN DIRI DI SMP PEMBANGUNAN LABORATORIUM UNP - Regia Amelia Putri; Fuji Astuti; Indrayuda Indrayuda (SENDRATASIK UNP, 2018)
AbstractThis study aimed: (1) to desribe the process of creation dance training based on environment in self-development activity at SMP Pembangunan Laboratorium UNP, (2) to describe the result of dance training based on environment in extracurricular activity in self-development activity in SMP Pembangunan Laboratorium UNP. The type of this study was qualitative with analytical descriptive method. In this dance arts based on environment on self-Improvement activity in SMP Pembangunan Laboratorium UNP, the dance training was done by using some steps, they were: (1) using auditif visual stimulation, (2) determining type of dance, (3) improvising gesture (4) evaluating the improvisation of students gesture, (5) selecting and doing rarefaction of students gesture. This training was done with some ways: (1) giving, introducing and understanding of nature and environment, (2) describing elements which exist in environment, (3) finding idea of dance based on participatory environment, (4) students found dance theme which divided into two groups, cleanness and afforestation groups, (5) eksploring dance gesture based on environment. Students who attended the self-development of dance were 13 of students. The result of this study showed that the dance training based on participatory environment on self-Improvement activity at SMP Pembangunan Laboratorium UNP was implemented properly. The creation dance consisted of two dances, namely the dance of  prohibition of took out trash carelessly and the dance of afforestation. This creation dance training based on participatory environment showed the result that students creativity in producing creative and innovative dance were confirmed, With this dance arts, the effort to save the environment and the continuous development could be helped and also the rarefection and sensitivity of the students also begun to be trained.Keywords: Dance creation, environment, self-development